The Ethics in Long-Term Care Model: Everyday Ethics and the Unseen Moral Landscape of Assisted Living. (April 2022) - Kemp, Candace L.; Lesandrini, Jason; Craft Morgan, Jennifer; Burgess, Elisabeth O.
Assisted living (AL) communities are long-term care settings where people live, work, and visit, and where social relationships and care, including end-of-life care, are negotiated. Assisted living is fraught with uncertainty and conflict about values, especially given residents' cognitive and physical frailty. These value-laden issues have implications for both resident and care partners' experiences. Yet, almost no research has examined ethics in this complex care environment. In this article, we draw on and synthesize existing theory, research, and practice knowledge to offer a conceptual model and discuss case examples that highlight everyday ethical issues in AL. We conceptualize the moral decision-making process and hence the moral landscape of AL, as influenced by a myriad of multi-level factors that shape interpersonal encounters and decision-making involving residents and their care partners, which ultimately shape individuals' actions and experiences in the setting. We conclude by discussing implications for research, policy, and practice.